Coarticulatory Aspects of the Fluent Speech of French and Italian People Who Stutter Under Altered Auditory Feedback - Verdurand, Marine; Rossato, Solange; Zmarich, Claudio (Frontiers in Psychology, 2020)
A number of studies have shown that phonetic peculiarities, especially at the coarticulation level, exist in the disfluent as well as in the perceptively fluent speech of people who stutter (PWS). However, results from fluent speech are very disparate and not easily interpretable. Are the coarticulatory features observed in fluent speech of PWS a manifestation of the disorder, or rather a compensation for the disorder itself? The purpose of the present study is to investigate the coarticulatory behavior in the fluent speech of PWS in the attempt to answer the question on its symptomatic or adaptive nature. In order to achieve this, we have studied the speech of 21 adult PWS (10 French and 11 Italian) compared to that of 20 fluent adults (10 French and 10 Italian). The participants had to repeat simple CV syllables in short carrier sentences, where C = /b, d, g/ and V = /a, i, u/. Crucially, this repetition task was performed in order to compare fluent speech coarticulation of PWS to that of PWNS, and to compare the coarticulation of PWS under a condition with normal auditory feedback (NAF) and under a fluency-enhancing condition due to an altered auditory feedback (AAF). This is the first study, to our knowledge, to investigate the coarticulation behavior under AAF. The degree of coarticulation was measured by means of the Locus Equations (LE). The coarticulation degree observed in fluent PWS speech is lower than that of the PWNS, and, more importantly, in AAF condition, PWS coarticulation appears even weaker than in the NAF condition. The results allow to interpret the lower degree of coarticulation found in fluent speech of PWS under NAF condition as a compensation for the disorder, based on the fact that PWS’s coarticulation is weakening in fluency-enhancing conditions, further away from the degree of coarticulation observed in PWNS. Since a lower degree of coarticulation is associated to a greater separation between the places of articulation of the consonant and the vowel, these results are compatible with the hypothesis that larger articulatory movements could be responsible for the stabilization of the PWS speech motor system, increasing the kinesthetic feedback from the effector system. This interpretation shares with a number of relatively recent proposal the idea that stuttering derives from an impaired feedforward (open-loop) control system, which makes PWS rely more heavily on a feedback-based (closed loop) motor control strategy.